2017
DOI: 10.1111/josh.12481
|View full text |Cite
|
Sign up to set email alerts
|

Combined Patterns of Risk for Problem and Obesogenic Behaviors in Adolescents: A Latent Class Analysis Approach

Abstract: The results confirm that obesogenic and HRBs should be conceptualized as combined patterns of risk. Health education programming in schools should adopt a multiple health behavior approach to target the continuum of risks adolescents engage in simultaneously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
43
1
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 74 publications
8
43
1
1
Order By: Relevance
“…In this study, low physical activity was also not a helpful indicator in determining the classes as it was highly prevalent in all classes (including the Healthy group); many children did not meet the recommended physical activity guidelines based on parent‐reported guidelines. This is contradictory to previous studies that found physical activity to be a determining characteristic for particular classes; however, this was in older children greater than 9 years of age 10,13–15 . Consistent with previous findings on clustering of risk behaviours, 13 this study found that the same class could exhibit both risk and protective behaviours, such as low physical activity but also low sedentary behaviour (screen time) exhibited by all classes except Class 1 and 3.…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…In this study, low physical activity was also not a helpful indicator in determining the classes as it was highly prevalent in all classes (including the Healthy group); many children did not meet the recommended physical activity guidelines based on parent‐reported guidelines. This is contradictory to previous studies that found physical activity to be a determining characteristic for particular classes; however, this was in older children greater than 9 years of age 10,13–15 . Consistent with previous findings on clustering of risk behaviours, 13 this study found that the same class could exhibit both risk and protective behaviours, such as low physical activity but also low sedentary behaviour (screen time) exhibited by all classes except Class 1 and 3.…”
Section: Discussioncontrasting
confidence: 86%
“…Some sex‐differences were observed, but there were also many similarities between the four classes that were identified separately in males and females. Of the six previous LCA studies, 10–15 four studies evaluated sex‐differences 11–13, 15 . Two of these studies 11,12 found that there were less girls in the high physical activity class compared with boys, while one study conversely found that girls were less likely to be in the high sedentary group compared with boys 10 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the relationship between long sleep duration and health-related behaviors has not been studied in depth, it seems that longer sleepers are more likely to report less screen time [8] and low PA levels [16]. Clustering sleep duration with other health-related behaviors may therefore contribute to a better understanding of health-related behavioral profiles in adolescents [17][18][19].The clustering pattern of PA, ST, sleep duration, diet quality, and sedentary screen time among children from 12 countries has been recently identified [20,21]. The retained profiles among children were characterized by: (a) mostly healthy behaviors (e.g., high PA, low sedentary screen time, healthy diet, and moderate/high ST), (b) mostly risk behaviors (e.g., low PA, moderate sedentary screen time, unhealthy diet, and high ST), and (c) co-occurrence of healthy and unhealthy behaviors (e.g., high PA, high sedentary screen time, high ST, and healthy, and unhealthy diet).…”
mentioning
confidence: 99%
“…Although the relationship between long sleep duration and health-related behaviors has not been studied in depth, it seems that longer sleepers are more likely to report less screen time [8] and low PA levels [16]. Clustering sleep duration with other health-related behaviors may therefore contribute to a better understanding of health-related behavioral profiles in adolescents [17][18][19].…”
mentioning
confidence: 99%